2003
DOI: 10.2174/1566523034578339
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Chloride Modified Silica Nanoparticles as a Non-Viral Vector with a High Efficiency of DNA Transfer into Cells

Abstract: Development of reliable vectors is a major challenge in gene therapy. Previous gene transfer methods using non-viral vectors, such as liposomes or nanoparticles, have resulted in relatively low levels (35 to approximately 50%) of gene expression. We have developed a silicon nanoparticle (SNAP) system, a novel non-viral vector, for DNA transfer into cells. SNAP was synthesized chemically and modified with sodium chloride or sodium iodide. Electronmicroscopy of SNAP and fluorescence microscopy of fluorescence-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 0 publications
0
50
0
Order By: Relevance
“…Coincubation of GC with gold nanoparticles (1) allowed nanoparticles to travel across GC membranes into organelles and potentially alter organelle ultrastructure, and (2) altered estradiol secretion/accumulation in a time-dependent manner. These are important observations since few studies have been published on translocation of nanoparticles into cells [18,[22][23][24][25][26][27], particularly cells of the female reproductive system. Researchers have reported movement of different types of nanoparticles to other areas of the body, but most of these studies described whole-animal studies with injection of nanoparticles or inhalation of these particles [16,18,23,28].…”
Section: Discussionmentioning
confidence: 99%
“…Coincubation of GC with gold nanoparticles (1) allowed nanoparticles to travel across GC membranes into organelles and potentially alter organelle ultrastructure, and (2) altered estradiol secretion/accumulation in a time-dependent manner. These are important observations since few studies have been published on translocation of nanoparticles into cells [18,[22][23][24][25][26][27], particularly cells of the female reproductive system. Researchers have reported movement of different types of nanoparticles to other areas of the body, but most of these studies described whole-animal studies with injection of nanoparticles or inhalation of these particles [16,18,23,28].…”
Section: Discussionmentioning
confidence: 99%
“…57 After uptake, nanoparticles can disseminate to different body tissues. [58][59][60][61] However, few toxicology studies are presently available.…”
Section: Toxicitymentioning
confidence: 99%
“…Recent studies have shown that administration of NPs to mice results in their accumulation in the various tissues including the brain and the testis. This indicates that they easily pass through the blood-brain and bloodtestis barriers [7,8]. Not all NPs will necessarily demonstrate an adverse effect leading to toxicity.…”
Section: Introductionmentioning
confidence: 99%